Peningkatan Nilai Tambah Kue Lapis Ubi Jalar Ungu Sebagai Upaya Diversifikasi Pangan (Studi Kasus: Dapoer Lopita) - Shalihy, Wildan; Dameswary, Amarilia Harsanti (Universitas Islam Madura, 2024)
Processing purple sweet potatoes is an effort to diversify food and increase the added value of purple sweet potatoes. By increasing the added value of purple sweet potatoes, it will increase the income of sweet potato farmers. This research aims to determine the added value analysis of processing purple sweet potatoes into processed products in the form of Dapoer Loepita purple sweet potato layer cake. Based on the calculation results of the added value analysis of using sweet potatoes as an ingredient in making purple sweet potato flour, an added value of Rp. -57,143.5 can be said to be a loss while making purple sweet potato layer cake produces an added value of IDR. 14.0019. Keyword: purple sweet potato,flour, diversification, Manokwari